PTU-048 What does open access endoscopy achieve: ten years on. (22nd June 2015) - Price, F; Vincent, N; Miah, R; Boulton, R
Abstract : Introduction: Guidelines for referral of patients with suspected upper gastrointestinal (GI) cancer were introduced by NICE in 2002, with the aim of detecting cancer early to improve survival. 1 We undertook a re-audit of GP referred OGDs performed under the NICE guidelines at the Queen Elizabeth Hospital, in one year and compared it to audit of 2002. 2 Our previous audit confirmed that in young patients without alarm symptoms endoscopy rarely found important pathology. 2 We predicted fewer OGDs in patients under fifty five years of age would be requested, and that by biassing our practice to an older patient group the relative yield of pathology would increase. Method: Retrospective analysis of 729 GP referred OGDs performed over one year. We collected age, referral reason (s) and outcome (s) for all OGDs. We correlated age with outcome and referral reason with outcome. Results: We found that we performed twenty five percent less OGDs in patients under fifty five years old than in the previous audit (39% vs. 29%, p-value 0.0001), despite this there was a decrease in the diagnosis of upper GI cancer (1% vs. 1.8%). There was no correlation between age and important pathology or referral reason and outcome. The commonest referral reasons were dysphagia, weight loss and dyspepsia. The commonest outcomes were a normal OGD, hiatus hernia and gastritis. Conclusion: There has been a statistically significant shift in the age distribution of patients undergoing OGD for suspected cancer and fewer young patients are referred, however this has not been associated with an increase in detection of important diagnoses, in fact the opposite has been shown. Our data suggests that a large proportion of open access GP referrals for OGDs do not detect any medically significant pathology, especially in patients under fifty five years. Disclosure of interest: None Declared. References: NICE. Referral Guidelines for suspected cancer. CG27. London, 2005 Sharma N, Kane K, Boulton R. What does open access endoscopy achieve?. Gut2002;50 :A9-A13, doi:10.1136/gut.50.suppl_2.a9